Land raising as a solution to sea‐level rise: An analysis of coastal flooding on an artificial island in the Maldives. (7th October 2019) - Brown, Sally; Wadey, Matthew P.; Nicholls, Robert J.; Shareef, Ali; Khaleel, Zammath; Hinkel, Jochen; Lincke, Daniel; McCabe, Maurice V.
Abstract: The Maldives (land elevation approximately 1 m above mean sea level) is often associated with the threat of rising sea levels. Land scarcity due to population pressure is also a major issue. In the late 1990s a new 1.9km 2 1.8 m high artificial island, Hulhumalé was created for urban expansion, including an allowance for sea‐level rise. This paper assesses flood exposure through an extreme water level scenario on Hulhumalé taking into account sea‐level rise and analyses potential adaptation options to extend island life. Results indicate that overtopping is likely to occur with 0.6 ± 0.2 m of sea‐level rise, with more severe, widespread flooding with 0.9 ± 0.2 m of sea‐level rise. If the Paris Agreement goals are met, flooding is not anticipated this century. However, under a non‐mitigation scenario, flooding could occur by the 2090s. Building seawalls 0.5, 1.0, and 1.5 m high could delay flooding for 0.2, 0.4, and 0.6 m of sea‐level rise, respectively. Land raising has been successful in Hulhumalé in reducing flood risk simultaneous to addressing development needs. Whilst new land claim and raising can be cost‐effective, raising developed land provides greater challenges, such as timeliness with respect to infrastructure design lives or financial costs. Thus the transferability and long‐term benefits of land raising requires further consideration.